El control de convecionalidad y el principio IURA NOVIT CURIA. Elementos para facilitar su entendimiento y aplicación. - Rosales Sánchez, Juan José (My University, 2021)
This doctoral thesis analyzes ex officio conventionality control in relation to the iura novit curia principle, aiming to redefine its understanding and simplify its application to improve human rights protection within the Mexican legal system . The research argues that the current application of conventionality control has failed to meet the expectations of the 2011 constitutional reform because it is often erroneously limited to a compatibility check between national norms and the Inter-American corpus iuris . By examining the Inter-American System, the Mexican system of constitutional control, and comparative elements from Spain, the author proposes that conventionality control should be understood through the lens of iura novit curia—the judicial duty to apply the valid law applicable to a case, which inherently includes international treaties, regardless of the parties' arguments. The study concludes that treating conventionality control not as a separate mechanism but as an integral part of the standard judicial method for applying valid law resolves current conceptual inconsistencies and maximizes the effectiveness of human rights guarantees .
CAPÍTULO I. PROTECCIÓN INTERNACIONAL DE LOS DERECHOS HUMANOS -- CAPÍTULO II. EL CONTROL DE CONVENCIONALIDAD EX OFFICIO EN EL SISTEMA INTERAMERICANO Y SU RECEPCIÓN EN LA DOCTRINA -- CAPÍTULO III. EL CONTROL DE LA CONSTITUCIONALIDAD Y LA CONVENCIONALIDAD EN MÉXICO -- CAPÍTULO IV. EL CONTROL DE LA CONSTITUCIONALIDAD Y LA CONVENCIONALIDAD EN ESPAÑA -- CAPÍTULO V. PROBLEMAS DERIVADOS DE LA FORMA DE ENTENDER Y APLICAR EL CONTROL DE CONVENCIONALIDAD -- CAPÍTULO VI. EL AFORISMO IURA NOVIT CURIA Y EL CONTROL DE CONVENCIONALIDAD -- CAPÍTULO VII. EL SISTEMA DE FUENTES DEL DERECHO EN MÉXICO -- CAPÍTULO VIII. ELEMENTOS PARA ENTENDER Y APLICAR DE OTRA FORMA EL CONTROL DE CONVENCIONALIDAD DIFUSO DERIVADOS DEL AFORISMO IURA NOVIT CURIA
Keywords: Derecho - Tesis; Unión Europea; Poder Judicial de la Federación.; Convención Americana sobre Derechos Humanos o Pacto de San José.; Conferencia sobre la Seguridad y la Cooperación en Europa.